The Selected Letters of Ezra Pound to John Quinn : 1915-1924 - Pound, Ezra, 1885-1972 (Book collections on Project MUSE., 1991)
This volume provides a first-hand survey of the arts and literature during a crucial period in modern culture, 1915-1924. Pound was then associated with such germinal magazines as BLAST, The Little Review, The Egoist, and Poetry; he was discovering or publicizing writers such as Robert Frost, Hilda Doolittle, T.S. Eliot, and James Joyce; and he was championing the painters Wyndham Lewis and William Wadsworth as well as the sculptors Jacob Epstein, Henri Gaudier-Brzeska, and Constantin Brancusi. Pound wrote to John Quinn-a New York lawyer, an expert in business law, and a collector of unusual.